Behaviour of high strength concrete column confined with steel strapping tensioning technique - Lee, Hoong Pin, 1986-, autho; Abdullah Zawawi Awang, 1964-, supervisor; Wahid Omar, Prof. Datuk Ir. Dr., 1962-, supervisor 606311; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam 619085 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2019